Контроль виконуваних екземплярів додатків в Windows 7/8/10 - Лобода, Євген Олександрович; Дубовий, Дмитро Олександрович (НТУ "ХПІ", 2017)
Розроблено програмний модуль визначання переліку процесів, що виконуються в комп’ютері і надання інформації про їх поточний стан, ідентифікатори й пріоритети виконання активних процесів, перелік задіяних dll бібліотек. Метою науково-дослідної роботи було розробити програмний модуль сумісний з різними останніми версіями операційної системи Windows, який вперше забезпечує за допомогою діалогового вікна отримання розширеної інформації про всі діючи додатки та надає можливість позбавлення від тих з них, що вийшли з під контролю. Проведено тестування зробленої розробки додатку.

A software module to determine the list of processes running on your computer and display information about their current status, IDs, perform the priorities list of used dll libraries. The aim of research was to develop a software module is compatible with a variety of the latest versions of the Windows operating system, which for the first time provides a dialog box to obtain extensive information on all executable applications and makes it possible to get rid of those that are out of control. Described sequentially all the steps of creating a conceptual project: carried out a detailed analysis of known attempts to accomplish the task; Described sequentially all the steps of creating a conceptual project: carried out a detailed analysis of the known attempts to perform the assigned tasks; We developed a method to obtain the optimal solution of the problem and justified project architecture with a given software functionality; logical design is made with the creation of the source code of software components and development of resources: physical design produced by running the executable. Functioning of the development has been tested on several versions of Windows. This testing fully confirmed the development operation, even when the process of getting rid of that came out under mortgaged for their control.
Control of the executable applications in Windows 7/8/10
Keywords: операційні системи; модуль; процес; ідентифікатор; пріоритет; тестування; module; process; operating system; control; ID; priority; testing